Cbl-b-deficient mice express alterations in trafficking-related molecules but retain sensitivity to the multiple sclerosis therapeutic agent, FTY720 - Fujiwara, Mai (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 Elsevier Inc. All rights reserved.